Penggunaan VUB Padi Untuk Pemanfaatan Lahan Bekas Tambang Pasir Kuarsa di Belitung Timur - Dede Rusmawan; Muzammil Muzammil (Politeknik Negeri Lampung., 2019)
The former quartz sand excavation land is a potential land for agricultural land. This land generally contains sufficiently high sand and very low fertility. The use of new superior varieties adaptive and tolerant can increase production. This study was carried out in the experimental field owned by BPTP in Gantong Village, East Belitung Regency, Bangka Belitung Islands Province. The design used was a randomized block design using three types of superior varieties, namely Inpari 22, Inpara 3, and Inpara 5. Each replication was repeated 3 times. Planting uses the jajar legowo system 4:1 (25 x 15) x 40 cm with 2-3 seedlings/planting holes. The fertilizer used is NPK 15:15:15 300 kg/ha and Urea 100 kg/ha. Urea fertilizer is given 3 (three) times each when plants are 7 days after planting (HST) as much as 25%, 25 HST as much as 50%, and 45 HST as much as 25% dose. Lime and organic fertilizer with a dose of 1 ton/ha each. Parameters observed included plant height, number of tillers, and production. The results of the study indicate that the growth of Inpara 5 has better than other varieties. The highest plant height and number of tillers are owned by Inpara 5, but not significantly different than Inpara 3 and Inpari 22. From the aspect of production Inpara 5 (2.23 t/ha) is significantly different from the varieties Inpara 3 (1.51 t/ha) and not significantly different from Inpari 22 (2.21 t/ha).